TINJAUAN YURIDIS TINDAK PIDANA PERDAGANGAN ORANG (HUMAN TRAFFICKING) DENGAN MODUS PENGANGKATAN ANAK SECARA ILEGAL ( STUDI KASUS PUTUSAN No . 275/Pid.Sus/2013/PN.Btl ) - , EMY FAJARINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The crime of human trafficking happen more frequently in Indonesia especially related to women trafficking and children, including baby. The victims are usually traded not only for sexual exploitation but also other exploitation forms so that human trafficking is one of the worst violation of human dignity and rights. Various modus were done by trafficker, one of them is illegally child adoption that is child adoption without asking legalization in court. Adoption has been regulated in legislation but the society didnât know about the rules, so the society were expected in the future know more about it rules as one of a way to anticipate the existence of the crime of human trafficking with illegally child adoption modus. The aim of internship is to obtain Diplome in Law degree and applied knowledge gained during following course. The benefits of internship such as the author can know various cases occuring in society and their solutions, one of them is the crime of human trafficking that often occurs in society so the author can understand about legal service and access to public. Judge consideration in making decision to the accused in case number 275/Pid.Sus/2013/PN.Btl more consider the juridical consideration than nonjuridical consideration. In this matter, author agrees with judge consideration in making decision in that case because judge choose the first alternative accusation that relevant and logic with act of the accused that already filled elements of Article 2 Paragraph (1) the Act number 21 of 2007 concerning Eradication of Human Trafficking Crime so act of the accused rightful can be categorized as the crime of human trafficking. Beside that, judge also already fulfilled the material and the formal elements of penal in making decision, so it has been suitable with the effective rules.